Studi Deskriptif Pengembangan Perilaku Disiplin dalam Pembelajaran PKN di Kelas V SD Negeri 08 Seberang Musi Kabupaten Kepahiang - Abdullah, Slamet (UNIB Press, 2024)
This research aims to (1) describe Civics learning planning in developing students' disciplinary behavior; (2) implementation of a planning program for developing student disciplinary behavior; and (3) assessment of the development of student disciplinary behavior. The approach and type of research used is descriptive qualitative. The data sources for this research are the deputy principal, teachers and students of SD Negeri 08 Seberang Musi. Data collection techniques use observation, interviews and documentation with data credibility testing through extended observations, member checks and negative case analysis. The data obtained was analyzed through data reduction, data display, and drawing conclusions. The results of this research are that in the planning stage the teacher plans the development of disciplinary behavior through integrating behavior in the RPP and designing a behavior habituation program. At the implementation stage, the development of students' disciplinary behavior appears in activities designed in the habituation activities carried out every day, including routine activities, spontaneous activities, modeling and conditioning. In the assessment stage, the teacher assesses the development of students' disciplinary behavior using behavior development journals and student behavior observation sheets in the learning process.